PEMAKAIAN WAP PADA TELEPON SELULER UNTUK BERITA ONLINE DAN SISTEM NAVIGASI GUNA PENCARIAN RUTE JALAN TERPENDEK - Haryanto . (Universitas Sahid Surakarta, 2010)
Development of mobile communication (handphone) since 1995 has been very fast. One of facilities that contributes the development is application of WAP (Wireless Application Protocol), namely, a protocol that is used to link with Internet via handphone. WAP provides support for application developers so that they are able to use it for connection with network. The advancement of technology makes possible to build WAP application by using WML (Wireless Markup Language) script that has a broader scope The technology progress provides solution and contribution in area of real time communication system. Therefore, the research is attempting to develop a new system that uses computer technology and communication technology, especially WAP-based technology as well as Djikstra algorithm. The new system will provide navigation system for travelers who are visiting Surakarta Town. The trip navigation systemcontains information related to trip routes of a traveler such as road condition and to know the shortest route of road to road or of location to location and also, the system displays alternative paths if there is an obstacle along the main road to destination. The easy accessibility of a trip to destination will make a system user to reach her or his destination quickly and correctly without he or she asks for helps to people along a road about direction of his or her destination.